2023
DOI: 10.1002/smll.202301594
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter‐Sized Single Crystals of Dion‐Jacobson Phase Lead‐Free Double Perovskite for Efficient X‐ray Detection

Abstract: Abstract2D Dion–Jacobson (DJ) phase hybrid perovskites have shown great promise in the photoelectronic field owing to their outstanding optoelectronic performance and superior structural rigidity. However, DJ phase lead‐free double perovskites are still a virgin land with direct X‐ray detection. Herein, we have designed and synthesized a new DJ phase lead‐free layered double perovskite of (HIS)2AgSbBr8 (1, HIS2+ = histammonium). Centimeter‐sized (18 × 10 × 5 mm3) single crystals of 1 are successfully grown via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Meanwhile, monovalent cations such as Ag + , Cu + , Cs + , and K + are commonly utilized in combination with Bi 3+ or Sb 3+ to form the double perovskite structures. , However, due to the large radius of iodide ions (I – ), the most common halogen anions in the reported three-dimensional (3D) Bi or Sb-based double perovskite structures are bromide or chloride ions (Cl – or Br – ). Therefore, it is challenging to combine I – with trivalent metal to form 3D double perovskite structures. On the other side, the emergence of two-dimensional double perovskites such as [AE 2 T] 2 AgBiI 8 , (C 6 H 16 N 2 ) 2 AgBiI 8 ·H 2 O, (C 6 H 16 N 2 ) 2 CuBiI 8 ·0.5H 2 O, and (3AMPY) 2 AgBiI 8 ·H 2 O have made it possible to obtain hybrid double perovskite iodides (HDPIs) through the dimensional reduction strategy. ,,, These HDPIs exhibit interesting material properties, such as ferroelectricity, light detection, ,,, X-ray detection, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, monovalent cations such as Ag + , Cu + , Cs + , and K + are commonly utilized in combination with Bi 3+ or Sb 3+ to form the double perovskite structures. , However, due to the large radius of iodide ions (I – ), the most common halogen anions in the reported three-dimensional (3D) Bi or Sb-based double perovskite structures are bromide or chloride ions (Cl – or Br – ). Therefore, it is challenging to combine I – with trivalent metal to form 3D double perovskite structures. On the other side, the emergence of two-dimensional double perovskites such as [AE 2 T] 2 AgBiI 8 , (C 6 H 16 N 2 ) 2 AgBiI 8 ·H 2 O, (C 6 H 16 N 2 ) 2 CuBiI 8 ·0.5H 2 O, and (3AMPY) 2 AgBiI 8 ·H 2 O have made it possible to obtain hybrid double perovskite iodides (HDPIs) through the dimensional reduction strategy. ,,, These HDPIs exhibit interesting material properties, such as ferroelectricity, light detection, ,,, X-ray detection, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Therefore, it is particularly important to explore new materials for superior-quality X-ray detectors. 14 Recently, halide perovskites have demonstrated remarkable application potential in the domain of direct X-ray detection owing to their large defect tolerance, low preparation cost, large atomic number, high resistivity, and large mobility–lifetime ( μτ ) product. 12,14 For instance, Yakunin et al reported the first halide perovskite X-ray detector that relied on CH 3 NH 3 PbI 3 polycrystalline films with a sensitivity of 25 μC mGy air −1 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskite materials have been developed over the past few decades, and they currently exhibit outstanding performance in solar cells, 7 photodetectors, 8 light-emitting diodes (LEDs), 9 lasers, 10 and nuclear radiation detectors 1,2,11,12 because of their large average atomic number, tunable bandgap, and high mobility-lifetime ( μτ ) products as well as relatively high resistivity. 13,14 In particular, all-inorganic lead halide perovskite CsPbBr 3 is useful in radiation detection due to its superior photoelectric properties, as well as satisfactory thermal and moisture stability.…”
Section: Introductionmentioning
confidence: 99%